Liquidity, Growth Opportunities, and Profitability as Determinants of Firm Value: Evidence from Manufacturing Companies from Indonesia - Hastalona, Dina; Tulim, Anto; Wahyuni, Rayu Sri; Pelawi, Pioner; Sitorus, Erbin (Golden Ratio of Finance Management, 2025)
Growth opportunity is a growth opportunity to invest in things that benefit the company. Therefore, a ratio is needed to assess the company's ability to pay all short-term debts with its current assets. This study aims to determine the effect of liquidity and capital structure on company value with profitability as a moderating variable in manufacturing companies and those listed on the Indonesia Stock Exchange in 2022-2024. The methodology in this study is quantitative research with secondary data in the form of financial reports listed on the Indonesia Stock Exchange (IDX) for 2022-2024, and the sample selection technique used is purposive sampling in 11 manufacturing companies. The sample was taken based on predetermined criteria using the purposive sampling method. The data that met the criteria amounted to 10 companies. The results of the F test state that liquidity and Growth opportunity have a simultaneous effect on company value. The regression results above show that liquidity positively affects company value. The greater the liquidity ratio, the more the company can pay short-term debts.  It can be concluded that liquidity influences decisions and assessments from external parties in a company so that it can maintain its financial performance and use its resources appropriately to increase its profits.